Add-on Ayurveda Treatment for Early Stage COVID-19: A Single Center Retrospective Cohort Study From Gujarat, India - Anup Thakar PhD; Kalpesh Panara PhD; Falgun Patel MD (Ayu); Shital Bhagiya PhD; Mandip Goyal PhD; Sagar Bhinde MD (Ayu); Swapnil Chaudhari PhD; Sarika Chaturvedi PhD (SAGE Publishing, 2021)
The retrospective cohort study aimed to evaluate the clinical outcomes of Ayurveda treatment exposure as an add-on to conventional care in early stage COVID-19 patients admitted at Samaras COVID care center, Ahmedabad, India. Conventional care included Vitamin-c, Azithromycin, and Paracetamol. Ayurveda formulations used as add-on were Dashamula and Pathyadi decoctions along with Trikatu powder , Sanshamani tablet, AYUSH-64 tablet AND Yastimadhu Ghana tablet for oral administration. Considering Add-on Ayurveda medicines as exposure of interest, patients who received Add-on Ayurveda medicines at least for 7 days were included in the exposed group while those who received only conventional care in unexposed group. Data was collected through record review and telephonic interviews. The outcomes of interest were the development of symptoms, duration of symptomatic phase in those progressing to symptomatic stage and mortality. Total 762 participants were included-[541 (71%) in the exposed group and 221 (29%) in the unexposed. Progression to symptomatic phase did not differ significantly between groups [27.6% in exposed, 24.6% in unexposed, adjusted RR 0.85; 95% CI 0.6-1.2]. The total duration of symptomatic phase among those progressing to the symptomatic stage was significantly decreased in the exposed group (x¯ = 3.66 ± 1.55 days in exposed (n = 133); x¯ = 5.34 ± 3.35 days in unexposed (n = 61), p < 0.001). No mortality was observed in either of the groups. Ayurveda Treatment as adjunctive to conventional care reduced the duration of symptomatic phase in early stage COVID-19 as compared to standalone conventional care. Add-on Ayurveda treatment has promising potential for management of early stage COVID-19.